Anatomy of a Semantic Context Interpreter with Real-time Events Notification Support - Maranhão, Guilherme Melo e; Sene Júnior, Iwens G.; Bulcão-Neto, Renato de Freitas (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2014: Proceedings of the 20th Brazilian Symposium on Multimedia and the Web, 2014)
In order to deal with the complexity of context-aware applications' development, the literature has reported an increasing demand for intelligent infrastructures which process heterogeneous context information and also provide real-time distributed communication. This paper outlines the Hermes software infrastructure to supporting the development of real-time, semantic context-aware applications. The main contribution is the anatomy of the Hermes Interpreter component in which the semantics of context is kept decoupled and context changes are notified in real-time. Benefits for applications developers include a reference architecture for context interpreters as well as the reuse of a complex infrastructure providing real-time distributed context notification. We have been working on a scenario of vital signs monitoring towards validating both the infrastructure and the interpreter component.